2023
DOI: 10.26668/businessreview/2023.v8i2.1538
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment Leadership as a Predictor of the Organizational Innovation in Higher Education

Abstract: Purpose: This study aims to examine the relationship between empowerment leadership and organizational innovation. This analyzes the influence of empowerment leadership on organizational innovation, whether knowledge sharing mediates the effect of empowerment leadership on individual creativity, if individual creativity moderates the influence of empowerment leadership on organizational innovation, and how psychological empowerment mediates the effect of leadership on individual creativity.   Theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…In particular, by demonstrating that empowering leadership is related positively to preoccupation with failure and, in turn, organizational exploration, we extend current research that showed that empowering leadership can affect vital components of organizational exploration, such as creativity (Han, 2022;Liu et al, 2020), experimentation, risk-taking, intelligence, and innovation (Kim et al, 2018;Kjellstr€ om et al, 2022;Naqshbandi et al, 2019;Rohlfer et al, 2022;Supriyanto et al, 2023;Tariq et al, 2022;Zhang et al, 2022a, b). In parallel, we add to current research regarding how managers can empower exploratory activities to achieve more valuable outputs, like increased employee inventive performance (Jiang et al, 2023) and enhanced sustainable economic performance (Faulks et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 72%
See 4 more Smart Citations
“…In particular, by demonstrating that empowering leadership is related positively to preoccupation with failure and, in turn, organizational exploration, we extend current research that showed that empowering leadership can affect vital components of organizational exploration, such as creativity (Han, 2022;Liu et al, 2020), experimentation, risk-taking, intelligence, and innovation (Kim et al, 2018;Kjellstr€ om et al, 2022;Naqshbandi et al, 2019;Rohlfer et al, 2022;Supriyanto et al, 2023;Tariq et al, 2022;Zhang et al, 2022a, b). In parallel, we add to current research regarding how managers can empower exploratory activities to achieve more valuable outputs, like increased employee inventive performance (Jiang et al, 2023) and enhanced sustainable economic performance (Faulks et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 72%
“…As per Schinazi et al (2022), empowerment can lead an individual to gain the confidence and strength to act upon one's life. Furthermore, recent research highlights the association of empowering leadership with both organizational innovation (Kim and Beehr, 2022;Naqshbandi et al, 2019;Supriyanto et al, 2023) and management innovation (Rohlfer et al, 2022).…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
See 3 more Smart Citations